STUDI KOMPARASI HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 PASAL 19 TENTANG PERLINDUNGAN KONSUMEN DALAM PEMBERIAN GANTI RUGI - Ajim Harahap, Zul Anwar; Nuraisyah, Nuraisyah (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
Diverse consumer needs spur businesses to provide various goods or services. Consumers easily fulfill their needs, but on the other hand consumers do not pay attention to the condition of the products offered by business actors. So, it is not uncommon for products received by consumers to cause material or physical losses. Compensation is a means that can be used to provide protection for consumers against defective products produced by business actors. The problem in this study is the comparison of rules in Islamic law and Law Number 8 of 1999 Article 19 concerning Consumer Protection, Equations and differences in compensation according to Islamic law and Law Number 8 of 1999 Article 19 concerning consumer protection. This study aims to determine the comparative rules in Islamic law and Law Number 8 of 1999 Article 19 concerning Consumer Protection, and to find out the similarities and differences in compensation according to Islamic law and Law Number 8 of 1999 Article 19 concerning consumer protection. The method used in this research is library research, which is a series of studies relating to library data collection methods, or research whose object of research is explored through various library information (books, insoklepedia, scientific journals, newspapers, magazines, and documents). The results of the research obtained indicate that compensation in Islam if it is related to soul or life, compensation is imposed on diyat, whereas if it relates to property, it will be subject to daman or compensation in the form of assets. While in Law Number 8 of 1999 concerning Consumer Protection, both losses involving the soul and property are all valued by assets (money). Both laws also provide provisions for compensation in the form of replacement of goods such as or similar, and both provide legal efforts to fulfill consumer rights. While the differences in Islamic law do not distinguish between early consumers and end consumers. Because consumers are all users of goods if the goods are used up directly or for further production. Whereas in Law Number 8 of 1999 concerning Consumer Protection that receives compensation is the final consumer